GENERAL GEOLOGY OF LIMESTONE IN THE F-FIELD OF CENTRAL LUCONIA WITH EMPHASIS ON PORE NETWORK MAPPING - Low, Zoann (Universiti Teknologi PETRONAS, 2014)
Dissolution has played a significant role in the modification of reservoir properties, specifically in the distribution of porosity and permeability within the carbonate bodies which directly affect reservoir performance. For rigorous reservoir characterization and performance prediction from petrophysical measurement, interpretation of the micropores behavior of different carbonate pore types is crucial due to its complex pore network. In order to improve our detail understandings of the pore behavior of the carbonate buildups in Central Luconia, a thorough investigation of the pore network was undertaken in two F-field wells from the Central Luconia Basin of Sarawak, Malaysia. The goal of this study was to testify the pore behavior of the carbonate rocks under several acid treatments by quantifying the changes of its pore geometry and spatial distribution of the rocks. Additional onshore carbonate analogue mapping in Sungai Siput, Perak was done prior to understand the offshore carbonate buildups. Core analysis to identify the offshore samples facies from drilled cores was done coherently with fabric classification using standard carbonate quantification manual. Initial pore network imaging and quantification of selective facies was then scrutinized through several petrographical analyses i.e. x-ray diffraction (XRD), thermal conductivity, energy dispersive x-raty (EDX), petrography, Poroperm, scanning electron microscopic analysis (SEM) and CT scan. Examination of post dissolution pore network like atomic absorption spectrometry (AAS) and CT-Scan were carried out after dissolution kinectics test was introduced. Results showed that carbonate rocks subjected to acid treatment on a prolong period of time exhibit prominent increment and enlargement in terms of pore geometry and spatial distribution.